(3eHGOF JShjb TQcGJ GdWjQGf (B/s - (3GdMhGQj, fVGd YHGSs; (3YhGO, GHQGgje NGdO s ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 2002)
(3ebOeI aj GdJShjb(B- (3HMhK GdJShjb(B- (3GdHjFI GdJShjbjI(B- (3JbSje GdShb(B- (3SdYI GdWjQGf(B- (3JcGdja Yed GdWGFQI(B- (3GdJSYjQ(B- (3eaghe GdJQhjL(B- (3bfhGJ GdJhRjY(B.s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdNWhW GdLhjIs